Features of the energy spectrum of cosmic rays above 2.5×1018 eV using the pierre auger observatory - Dova M.T. (2020)
We report a measurement of the energy spectrum of cosmic rays above 2.5×1018 eV based on 215 030 events. New results are presented: at about 1.3×1019 eV, the spectral index changes from 2.51±0.03(stat)±0.05(syst) to 3.05±0.05(stat)±0.10(syst), evolving to 5.1±0.3(stat)±0.1(syst) beyond 5×1019 eV, while no significant dependence of spectral features on the declination is seen in the accessible range. These features of the spectrum can be reproduced in models with energy-dependent mass composition. The energy density in cosmic rays above 5×1018 eV is [5.66±0.03(stat)±1.40(syst)]×1053 erg Mpc-3. © 2020 authors. Published by the American Physical Society. Published by the American Physical Society under the terms of the "https://creativecommons.org/licenses/by/4.0/"Creative Commons Attribution 4.0 International license. Further distribution of this work must maintain attribution to the author(s) and the published article's title, journal citation, and DOI.